Synthesis of Molecular Hybridization Based Aromatic linked Naphthalimide-Benzimidazole Conjugates - Chhikara, Akanksha (My University, 2018)
Cancer is the biggest problem of health, fear throughout the world. Number of deaths due to cancer is increasing day by day worldwide, especially in the developing countries. Thus, there is a great need to create precisely new anticancer candidate that can bind to various biological targets effectively. Here, we have synthesized aromatic linked naphthalimide-benzimidazole conjugates using molecular hybridization methodology. These compounds are characterized by 1H and 13C NMR spectroscopy. These compounds will further be used for the evaluation for anti-proliferative activity as well as DNA interaction studies.
Keywords: Molecular Hybridization; Benzimidazole; Naphthalimide; conjugation